A case of hyperprolactinaemia in a patient with metastatic melanoma. Issue 3 (June 2021) - Manning, Annie; Rassie, Kate; Rivalland, Gareth
Abstract : Ectopic prolactin production from a malignancy is infrequently reported. We report here a 60-year-old gentleman who presented with hyperprolactinaemia (9100 mIU/L) causing expressible galactorrhoea, decreased libido and fatigue thought to be due to ectopic prolactin secretion from a metastatic melanoma. Upon initiation of pembrolizumab, the patient's symptoms resolved and he became normoprolactinaemic. This corresponded with a partial response on radiological imaging. Although the core biopsy of the metastatic melanoma did not exhibit immunostaining for prolactin, we believe that only a subset of the tumour cells possesses prolactin-secreting capacity. This case illustrates the need to consider ectopic prolactin production for a solid malignant tumour as a rare cause of hyperprolactinaemia in patients with a normal pituitary MRI, in the absence of other causes.